GAP analýza systému řízení bezpečnosti informací - Konečný, Martin (Vysoké učení technické v Brně. Fakulta podnikatelská, 2019)
Diplomová práce se zaměřuje na GAP analýzu systému řízení bezpečnosti informací. Práce se skládá z teoretické, analytické a praktické části. První část pojednává o teoretických východiscích problematiky informační a kybernetické bezpečnosti. Analytická část popisuje současný stav ve zkoumané společnosti. Výstupem práce je návrh registru rizik a návrh zavedení bezpečnostních opatření. Návrh cílí na opatření vedoucí k zvýšení bezpečnosti informací ve společnosti

The master’s thesis focuses on GAP analysis of information security management system. The thesis consists of theoretical, analytical and practical part. The first part discusses the theoretical background of the issue of information and cyber security. The analytical part describes the current condition of the researched company. The thesis’s output is the draft of risk register and draft of security countermeasures implementation. The draft targets on countermeasures leading to increase information security in company.
GAP analysis of information security management system
Keywords: informační bezpečnost; kybernetická bezpečnost; GAP analýza; systém řízení bezpečnosti informací; ISO/IEC 27000; analýza rizik; opatření; bezpečnostní politiky; registr rizik; Information security; cyber security; GAP analysis; information security management system; ISO/IEC 27000; risk analysis; countermeasures; security policy; risk register